Numerical analysis of storm tide levels with wave setup in Batanes Islands during Typhoon Meranti 2016 - Turiano, Marjorie C.; Cruz, Eric C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The recent November 2013 Typhoon Haiyan event demonstrated that storm surges can cause devastating damages to both life and property. Given this knowledge, further research regarding numerical modeling of storm surges in the country becomes imperative. Recent research demonstrated that the contribution of wave setup to the total storm tide level is significant and must be considered in numerical modeling. This research ultimately aims to quantify the contribution of waves to the storm surge height by utilizing a coupled hydrodynamic-wave numerical model to simulate the storm tide levels during the September 2016 Typhoon Meranti event in Batan and Sabtang Islands, Batanes. Typhoon Meranti was one of the strongest typhoons that made landfall in the Philippines in 2016, with intensity comparable to that of the 2013 Typhoon Haiyan. The numerical storm tide model for the study area was developed using the two way coupled Delft3D-SWAN models. The simulated storm tide levels were validated against observations from a tide monitoring station in Basco Port, and compared to the findings of a post-disaster Survey conducted in the study area. The observed peak water level in Basco Port during the passage of Typhoon Meranti is only 0.87m above MSL. The simulated peak storm tide level in Basco Port is 0.72 m above MSL, 0.19 m (26 percent) of which is due to waves. The primary factors that affect the Storm tide level were identified to be the atmospheric forcing, the astronomic tide levels, and the wave conditions. The correctness of the modeling of these factors was demonstrated to qualify the accuracy of the simulated Storm tide levels. Tropical cyclone analyses showed that the radius of maximum winds was best estimated using the relation given by Vickery and Wadhera (2008). The parametric cyclone model by Fujita (1952) best estimated the observed sea level pressures, while the model by Holland et al. (2010) was superior in terms of modeled surface winds. The hydrodynamic model was calibrated such that the simulated astronomic tide levels match the forecast water levels given by WXTIDE. The results of the wave model showed very good agreement with the parametric wave estimates given by CEM (2005). The numerical analyses showed that the contribution of waves can reach up to 0.8 m, or contribute up to 90 percent of the surge height in the study area. Storm Surge heights in points located on the west coasts of the islands are 25 percent to 60 percent due to wave effects, while storm surge heights on the east coasts are 60 percent to 90 percent due to wave effects. Points on the west coasts experience peak water levels when the typhoon was nearest the study area, while points on the east coasts experience peak water levels approximately seven hours earlier. The findings of this research are useful in the forecasting of expected peak storm tide levels for disaster risk management and urban planning. Knowledge of the contribution of waves to the peak storm tide elevations also improves the accuracy of design water levels for the vertical siting of coastal Structures during conceptual and detailed engineering design Stages.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Storm surges -- Mathematical models; Storm surges -- Philippines -- Batanes; Ocean waves; Storm tide